2018
DOI: 10.1007/s00604-018-2827-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric determination of the activity of alkaline phosphatase based on the competitive binding of gold nanoparticles and pyrophosphate to CePO4:Tb nanorods

Abstract: A fluorometric method is described for the determination of the activity of alkaline phosphatase (ALP). It relies on the competition between gold nanoparticles (AuNPs) and pyrophosphate (PPi) for the coordination sites on the surface of CePO:Tb nanorods. The green fluorescence of the CePO:Tb is reduced in the presence of AuNPs due to fluorescence resonance energy transfer (FRET), but can be restored on addition of PPi due to the stronger affinity of PPi to the CePO:Tb. In the presence of ALP, PPi is hydrolyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Due to the fact that the ALP activity can be inhibited by Na 3 VO 4 , PPi cannot be hydrolyzed into PO 4 3– by ALP; the more Na 3 VO 4 that is added, the more ALP activity that is inhibited and the more P 2 O 7 :Ce,Tb nanoparticles that remained, leading to the stronger fluorescence. It can be seen from Figure d that the fluorescence was enhanced gradually with the increasing Na 3 VO 4 concentration, suggesting that the suppression efficiency was promoted by the increased Na 3 VO 4 concentration, and the half-maximal inhibitory concentration (IC 50 ) was calculated to be 65 μM (inset of Figure d), which is comparable with the reported results (Table S1) and demonstrated that the present approach can be used for not only ALP activity detection but also ALP inhibitor screening …”
Section: Resultssupporting
confidence: 86%
“…Due to the fact that the ALP activity can be inhibited by Na 3 VO 4 , PPi cannot be hydrolyzed into PO 4 3– by ALP; the more Na 3 VO 4 that is added, the more ALP activity that is inhibited and the more P 2 O 7 :Ce,Tb nanoparticles that remained, leading to the stronger fluorescence. It can be seen from Figure d that the fluorescence was enhanced gradually with the increasing Na 3 VO 4 concentration, suggesting that the suppression efficiency was promoted by the increased Na 3 VO 4 concentration, and the half-maximal inhibitory concentration (IC 50 ) was calculated to be 65 μM (inset of Figure d), which is comparable with the reported results (Table S1) and demonstrated that the present approach can be used for not only ALP activity detection but also ALP inhibitor screening …”
Section: Resultssupporting
confidence: 86%
“…The limit of detection for ALP was estimated to be 0.08 U/L according to 3σ rule. In comparison with the previously reported ALP detection method (Table 1), the proposed method has lower detection limit and is more cost-effective [30][31][32].…”
Section: Determination Of Alp Activity By the Proposed Methodsmentioning
confidence: 80%
“…This approach is extremely sensitive with 0.06 U L −1 limit of detection (LOD) within the linear range from 0.2 to 100 U L −1. 72 …”
Section: Nano Probesmentioning
confidence: 99%